An argumentation framework with backing and undercutting - Cohen, Andrea (2011)
In this work we will combine two important notions for the argumentation community into Abstract Argumentation Frameworks (AFs). These notions correspond to Toulmin’s backings and Pollock’s undercutting defeaters. We will define Backing-Undercutting Argumentation Frameworks (BUAFs), an extension of AFs that includes a specialized support relation, a distinction between different attack types, and a preference relation among arguments. Thus, BUAFs will provide a more concrete approach to represent argumentative or non-monotonic scenarios where information can be attacked and supported